Application of Digital Simulation-Based Gamification to Improve Learning Outcomes of Grade IV Students in Natural and Social Sciences Subjects - Nita, Cicilia Ika Rahayu; Arbaini, Anggia Disbi; Ningsih, Puji Rahayu (Melior : Jurnal Riset Pendidikan dan Pembelajaran Indonesia, 2025)
This study aims to improve the learning outcomes and active participation of fourth-grade students at Kebonsari 2 Public Elementary School in Natural and Social Sciences learning through the implementation of gamification strategies. The background of this research is the low student motivation and learning achievement caused by the predominance of conventional teaching methods that lack appeal and fail to engage students actively. The research employed a classroom action research model based on the spiral framework developed by Kemmis and McTaggart, conducted over two cycles. Data were collected through diagnostic tests, observations, interviews, and documentation, and analyzed quantitatively using descriptive statistics and N-Gain analysis to measure improvement. The intervention included the integration of gamification elements such as buying and selling simulation games for economic activity topics, augmented reality-based media to explore the surrounding environment, and a tiered challenge system in student worksheets to enhance motivation and engagement. The findings revealed an increase in the average score of student learning outcomes from 61.15 in the pre-cycle to 84.81 in the second cycle. The percentage of students achieving mastery learning rose from 30.77 percent to 92.31 percent. The average N-Gain score of 0.66 indicates a moderate to high level of improvement, affirming the effectiveness of gamification strategies. Theoretically, the study supports the application of gamification as a pedagogical approach aligned with the learning preferences of the digital-native generation.